The Bluebook uncovered : a practical guide to mastering legal citation : (twentieth edition of the Bluebook) - Anthon, Dionne E (American casebook series, 2015)
"This book is designed to help first-year law students master the fundamental Bluebook citation rules that will be needed in legal research and writing courses (LRW) and in legal practice. It can also act as a Bluebook refresher for other law students, clerks, attorneys, judges, and paralegals"--P. xi.